Appointment of new DLSU's Reserve Officers' Training Corps commandant - De La Salle University, Manila (Animo Repository, 1993)
Capt. Januario Caringal replaced outgoing Lieutenant William de Leon as DLSU's Reserve Officers' Training Corps (ROTC) Commandant.